MENGEDUKASI ANAK ANAK PESISIR SIMANINDO DALAM MENCEGAH PERUNDUNGAN (BULLYING) DILINGKUNGAN ANAK - Ester Sitindaon; Tuti Atika (JOURNAL SAINS STUDENT RESEARCH, 2024)
Education plays a central role in shaping the character of children, particularly among the coastal children of Simanindo who encounter the unique realities of coastal life and the wisdom of local culture. This article aims to investigate the role of education in preventing bullying among coastal children in Simanindo. Recognizing the cultural richness and proximity to the marine environment, relevant and effective educational strategies become crucial. A literature review approach is employed to delve into a comprehensive understanding of the challenges of bullying and the distinctive context of Simanindo's coastal children. The results emphasize the need for integrating local wisdom into the curriculum, emphasizing the strengthening of moral values, and engaging the community to create an educational environment that supports both learning and bullying prevention. This article contributes to the understanding of the role of education in shaping the character of Simanindo's coastal children and designing educational strategies that align with their social and cultural context.